Human resource development in tourism: principles and practices - Swain, Sampad Kumar (Delhi Abhijeet Publications, 2006)
Study with special reference to Orissa, India.
Includes bibliographical references and index
Keywords: Tourism -- India -- Orissa; Industrial relations -- India -- Orissa; Personnel management -- India -- Orissa